Effects of Four Compounds from Gentianella acuta (Michx.) Hulten on Hydrogen Peroxide-Induced Injury in H9c2 Cells. (20th January 2019) - Ren, Kai; Su, He; Lv, Li-juan; Yi, Le-tai; Gong, Xue; Dang, Lian-sheng; Zhang, Rui-fen; Li, Min-hui
Abstract : In previous studies, Gentianella acuta (Michx.) Hulten was reported to contain xanthones, iridoids, terpenoids, and sterols and is mainly used to cure hepatitis, jaundice, fever, headache, and angina pectoris. In this study, we used bioassay guided fractionation to identify compounds from G. acuta and investigated their activity against hydrogen peroxide (H2 O2 )-induced apoptosis of H9c2 cells using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) method. The levels of nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase-1 (HO-1), and glutamate-cysteine ligase catalytic (GCLC) expression were assessed using quantitative real-time polymerase chain reaction (qRT-PCR). Protein expression was evaluated using western blot. The results showed that all four compounds had protective effects on H9c2 cells. The transcription levels of HO-1 and GCLC significantly increased in H9c2 cells pretreated with norswertianolin (1 ), swetrianolin (2 ), demethylbellidifolin (3 ), and bellidifolin (4 ). However, compared to the model group, the transcription levels of Nrf2 were not enhanced by pretreatment with compounds1, 2, and4 . The protein expression levels of HO-1 and GCLC in H9c2 cells were greater than that in the H2 O2 -treated group, and the expression of Nrf2 was not significantly changed except by swetrianolin treatment; inhibitors can reverse the protective effect by ZnPP (15  μ M), BSO (10  μ M), and brusatol (10  μ M). The results indicated that the four compounds isolated from G. acuta inhibited the oxidative injury induced by H2 O2 by activating the Nrf2/ARE pathway in H9c2 cells and provide evidence that G. acuta may be a potential therapeutic agent for the treatment of cardiovascular diseases.